A mixed methods study to explore women and clinician׳s response to pain associated with suturing second degree perineal tears and episiotomies [PRAISE]. Issue 4 (April 2015) - Briscoe, Lesley; Lavender, Tina; O׳Brien, Ediri; Campbell, Malcom; McGowan, Linda
Abstract: Background: perineal suturing is a common event which affects women across a variety of international settings. Women have expressed pain related to perineal trauma in the postnatal period but little is known about pain during suturing. In addition, there is a lack of evidence to identify how professional decisions are made about pain management during the suturing process. Objective: to explore women and clinician׳s response to pain during the suturing of second degree tears and episiotomies. Design: mixed method feasibility study which included observation, questionnaires and interviews. Setting: a Hospital Trust in Northwest England. Participants: 40 women and 21 clinicians participated. Measurements and findings: mild, moderate and severe pain was measured via the McGill Pain Questionnaire-Short Form (MCPQ-SF). Psychological distress was identified via the Hospital Anxiety and Depression Scale (HADS). Semi-structured face to face interviews identified three themes, Psychological distress and future functioning; Variation in practice and Style of communication. Key conclusions: women who experienced psychological distress during previous or current childbirth scored higher on HADS and MCPQ-SF, and appeared to express more concerns about future functioning and healing. Variation in practice exists and style of communication had the potential to make the difference for women. Implications for practice and research: the process of suturing is complex and is not a standalone event for a woman. It is crucial that health professionals consider previous and subsequent experience of perineal suturing. Future research aims to develop a decision tree to support pain management during suturing. Highlights: Women who scored higher on measures of self-reported pain and psychological distress had experienced a previous psychologically distressing event and were concerned about future functioning. Variation in practice occurred around how health professionals managed women's pain The style of communication had the ability to increase women's satisfaction about perineal suturing